2019
DOI: 10.1080/13506285.2019.1581316
|View full text |Cite
|
Sign up to set email alerts
|

Feature guidance by negative attentional templates depends on search difficulty

Abstract: Running head: Negative templates and search difficulty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 35 publications
(57 reference statements)
1
56
2
Order By: Relevance
“…However, given that only a handful of studies examined markers of active preparatory suppression, it is premature to conclude that direct top‐down inhibition in either the spatial or feature domain is not possible. One intriguing possibility is that in contrast to preactivating an attentional template, preparatory suppression is cognitively demanding and therefore limited to contexts of especially difficult searches . Future studies that examine the effect of search difficulty on distractor inhibition at the neural level are necessary to test the idea that advance distractor suppression may selectively occur in cognitively demanding situations, and whether alpha contributes to this.…”
Section: Direct Preparatory Distractor Suppressionmentioning
confidence: 99%
“…However, given that only a handful of studies examined markers of active preparatory suppression, it is premature to conclude that direct top‐down inhibition in either the spatial or feature domain is not possible. One intriguing possibility is that in contrast to preactivating an attentional template, preparatory suppression is cognitively demanding and therefore limited to contexts of especially difficult searches . Future studies that examine the effect of search difficulty on distractor inhibition at the neural level are necessary to test the idea that advance distractor suppression may selectively occur in cognitively demanding situations, and whether alpha contributes to this.…”
Section: Direct Preparatory Distractor Suppressionmentioning
confidence: 99%
“…However, given that only a handful of studies examined markers of active preparatory suppression, it is premature to conclude that direct top-down inhibition in either the spatial or feature domain is not possible. One intriguing possibility is that in contrast to pre-activating an attentional template, preparatory suppression is cognitively demanding and therefore limited to contexts of especially difficult searches (55). Future studies that examine the effect of search difficulty on distractor inhibition at the neural level are necessary to test the idea that advance distractor suppression may selectively occur in cognitively demanding situations, and whether alpha contributes to this.…”
Section: Direct Preparatory Distractor Suppressionmentioning
confidence: 99%
“…Divergent findings have been reported regarding whether distractor cues can accelerate search efficiency (Arita, Carlisle, & Woodman, 2012;Beck & Hollingworth, 2015;Becker, Hemsteger, & Peltier, 2015;Olivers, 2009;Soto, Heinke, Humphreys, & Blanco, 2005;Geoffrey F Woodman & Luck, 2007). Among the studies that showed behavioral promotions, the emergence of suppression benefits seemed to be dependent on multiple factors (Conci, Deichsel, Müller, & Töllner, 2019;Han & Kim, 2009;Stilwell & Vecera, 2019;Tanda & Kawahara, 2019;Töllner, Conci, & Müller, 2015), especially the constancy of distractor cues across trials so as to form expectations (Cunningham & Egeth, 2016;Gaspelin, Leonard, & Luck, 2015;Gaspelin & Luck, 2018a;Vatterott & Vecera, 2012;Wen, Hou, & Li, 2018, for reviews, see Gaspelin & Luck, 2018bNoonan, Crittenden, Jensen, & Stokes, 2018;van Moorselaar & Slagter, 2020).…”
Section: Introductionmentioning
confidence: 99%